Psychometric properties of the Persian version of the quality of recovery-15 questionnaire - Hooman Shahsavari; Golnar Ghane; Shahrzad Ghiyasvandian; Masoumeh Zakerimoghadam; Fatemeh Najafi (SpringerOpen, 2021)
Abstract Background Recovery after surgery is a complex process since it depends on many factors, such as the patient's sex, age, surgery type, and presence of other diseases. This study aimed to translate and evaluate the psychometric properties of the Persian version of the quality of recovery-15 (QoR-15) questionnaire in Iranian patients undergoing surgery. Methods The Persian version of the QoR-15 questionnaire was developed after translating and culturally validating the instrument. Content validity was assessed with a sample of clinicians (n = 15) and face validity was assessed in a sample of patients (n = 15) undergoing elective surgery. The final questionnaire was completed by 450 patients (n = 450) 24 h after surgery. Construct validity was assessed using exploratory factor analysis in patients (N = 250). Convergence and divergent validity were also assessed. Internal consistency was assessed using Cronbach's alpha and construct reliability was also assessed. Test-retest reliability was assessed on a randomly selected sub sample of 50 patients. Finally, the questionnaire was completed by a further sample of 200 patients 24 h after surgery and construct validity was assessed using confirmatory factor analysis. Results According to Lawshe, all items received at least an acceptable ratio for content validity ratio (CVR). Item content validity index (I-CVI) of each item was greater than 0.79. Construct validity indicated good fit statistics in the five components of CFA, and CFI was > 0.93. The reliability of the QoR-15 questionnaire was acceptable based on Cronbach's alpha score (> 0.001), test-retest reliability value (0.81), and CR (> 0.7). Conclusion The Persian version of the QoR-15 questionnaire was equivalent to the original one regarding both conceptual and linguistic aspects. This study also confirmed the validity and reliability of the Persian version of the QoR-15 questionnaire. Therefore, the Persian version of the QoR-15 questionnaire can be a suitable and brief instrument to assess the recovery quality in Iranian patients undergoing surgery.